2006
DOI: 10.1590/s0037-86822006000200013
|View full text |Cite
|
Sign up to set email alerts
|

Triatomíneos rupestres infectados por Trypanosomatidae, coletados em Quaraí, Rio Grande do Sul, 2003

Abstract: ARTIGO/ARTICLEAtualmente, após as campanhas de combate ao Triatoma infestans e sua conseqüente eliminação do domicílio e peridomicílio, triatomíneos silvestres estão se candidatando a assumir a condição de vetores do Trypanosoma cruzi no ambiente domiciliar 22 .Triatoma rubrovaria, espécie silvestre, hoje encontrada no Brasil apenas nas regiões do centro ao sul e oeste do Estado do Rio Grande do Sul 14 15 , aparentemente, nas proximidades das residências, está ocupando o espaço anteriormente colonizado pelo T.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 7 publications
0
10
0
2
Order By: Relevance
“…We emphasize that T. rubrovaria presents bionomic characteristics of a good vector of T. cruzi (Almeida et al 2000(Almeida et al , 2002a(Almeida et al ,b, 2003(Almeida et al , 2005 and can maintain high rates (25%) of natural infection by that parasite (Martins et al 2003(Martins et al , 2008. According to Jurberg et al (1998), T. carcavalloi can also invade human domiciles.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We emphasize that T. rubrovaria presents bionomic characteristics of a good vector of T. cruzi (Almeida et al 2000(Almeida et al , 2002a(Almeida et al ,b, 2003(Almeida et al , 2005 and can maintain high rates (25%) of natural infection by that parasite (Martins et al 2003(Martins et al , 2008. According to Jurberg et al (1998), T. carcavalloi can also invade human domiciles.…”
Section: Discussionmentioning
confidence: 88%
“…Almeida et al (2002a) observed that three triatomine species (T. carcavalloi, T. rubrovaria, and T. circummaculata; Figure 1) occur in sympatry in the same ecotope (rock piles) in RGS. All of them have also been found inside domiciles in this state (Martins et al 2003, Jurberg et al 1998). Jurberg et al (1998) …”
Section: Introductionmentioning
confidence: 82%
“…Studies carried out in many different regions of Brazil have shown high triatomine infestation on palms, chiefly by bugs of the genus Rhodnius spp. 9,19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Field data have shown that T. rubrovaria is frequently found in domiciliary and peridomiciliary areas 3 . Only T. carcavalloi has been observed in Canguçu, Dom Feliciano, Pinheiro Machado and São Jerônimo 4 (Source: IPB-LACEN/RS), appearing inside domiciles throughout Rio Grande do Sul 5,6 .…”
Section: Introductionmentioning
confidence: 99%